Adverse Reactions after Administration of Antivenom in Korea - Jin Seok Shim (Toxins, 2020)
Kovax® antivenom is the main treatment for toxins produced by the Gloydius species. However, research on adverse reactions after Kovax® antivenom administration is scarce. We aimed to identify the incidence and characteristics of adverse reactions after Kovax® antivenom administration. We conducted a retrospective review of the medical records of snakebite patients in Korea between January 2008 and September 2019. We identified the frequency, characteristics, and treatments of adverse reactions to Kovax® antivenom. There were 150 patients with snakebites, of whom 121 (80.7%) patients received Kovax® antivenom. Adverse reactions occurred in five patients (4.1%). Acute adverse reactions within 24 h of antivenom administration occurred in two patients (1.7%). The symptoms of patients with acute adverse reactions were nausea, diaphoresis, dizziness, and hypotension. Delayed adverse reactions that occurred 24 h after antivenom administration were reported in three patients (2.5%). One patient had a skin rash after 10 days, and two patients had fever 37 and 48 h after antivenom use. In conclusion, most patients were managed safely after Kovax® antivenom, and the incidence of adverse reactions was low. Severe adverse reactions occurred in a small percentage of patients, and there were no deaths.